Sports business management decision making around the globe - Foster, George 1948-; O'Reilly, Norm, 1973-; Davila, Antonio (London Routledge, Taylor & Francis, 2016)
Sports Business Management will equip students with a comprehensive understanding of the sport industry. With a focus on management, strategy, marketing, and finance, the decision-making approach of the book emphasizes key concepts while translating them into practice. Foster, O'Reilly, and Davila present a set of modular chapters supported with plenty of examples, mini-cases, and exercises to help students apply the decision-making approach to real-world situations. Covering an international array of sports and organizations - including the Olympic Games, FIFA World Cup, US Major League Baseball, and more - the book also covers unique topics such as diversity in sport, the impact of technology, and social media. Rounding this out, the book provides around 50 Harvard / Stanford cases, along with case notes for instructors.
Part I: Introduction to Sports Business Management 1. Decision Making: A Structured Approach 2. The World of Sports and Its Business Ecosystem Part II: Stakeholders 3. Leagues 4. Clubs, Owners and Management 5. Professional Athletes and Players Associations/Unions 6. Club Player Side Decision Making 7. Global Sporting Bodies, Federations and Associations 8. College Sports 9. Sporting Events and Mega-Events Part III: Applications 10. Sport Marketing 11. Sport Sponsorship 12. Athlete Sponsorship, Endorsement and Branding 13. Ticket Pricing and Venue-Related Revenue Streams 14. Building Sports Engagement 15. Sport Broadcasting: Content and Distribution Decisions 16. SportBroadcasting (2): National and Regional Sport Networks 17. New Venue Building and Venue Management 18. Valuation of Clubs, Companies, and Other-Sporting Related Assets.
Includes bibliographical references and indexes.
Keywords: Sports administration; Sports -- Marketing